Tourism’s Driving Forces On Land Use Change In Phu Kradueng National Park, Thailand - Mayuree, Nasa (2020)
In recent years, many national parks have faced tension caused by the rapid growth of nature-based tourism. Tourism has not only affected the national parks, but beyond the trans-boundary of the neighbouring land area, or it is known as the periprotected area. Although there has been a growing demand for tourism in the protected area, previous studies investigating the impacts of tourism’s driving forces on this area are still limited and the term peri-protected area is seldom used. Thus, it is crucial to further study on tourism’s driving forces and their impact on this special area at the national park as well as surrounding local communities. The objectives are to investigate land use patterns in the peri-protected area and the roles of the impact of tourism’s driving forces on land use. A mixed methodology was used to facilitate data collection and analysis. The quantitative approach used the GIS program to analyse the land use pattern and land use change over the three periods of the peri-protected area. The current research employed an online self-administered questionnaire survey based on Dickman’s 5As of tourist destination concept to collect data from 465 tourists and SPSS were employed to analyse the descriptive statistics. For the qualitative approach, semi-structured interviews were conducted with a total of 77 key informants representing different groups of people who were associated with land use change in the peri-protected area. The findings revealed that there was a gradual change in land use patterns based on the conservation and tourism policy implementation in the Phu Kradueng National Park (PKNP) and land use was classified into four zones.